2018
DOI: 10.1039/c8rp00104a
|View full text |Cite
|
Sign up to set email alerts
|

Developing an understanding of undergraduate student interactions in chemistry laboratories

Abstract: Laboratories play a crucial role in the undergraduate science curriculum and the effectiveness of learning in laboratories is influenced by learners’ interactions with other students, the instructors, and the equipment used. In this study, a pre-lab survey was used to collect information about students’ expectations of interactions in chemistry laboratories and how they can be ranked according to their importance. Post-lab surveys were used to capture students’ perspectives about the frequency of interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…While physical laboratories have been well researched from theoretical perspective through multiple types of student interactions (Komorek & Kattmann, 2008 ; Wei et al., 2018 ), such studies on remote laboratories are sparse (Wei et al., 2019 ). The significant contributions of this paper are (1) designing a remote lab such as RT-UTM that allows greater flexibility in performance of 5 experiments in comparison to its equivalent physical UTM lab, (2) capturing the structure and interactivity of PL-UTM and RT-UTM through the Transactional distance theory (TDT) and ultimately (3) conceptual understanding in remote vs physical and integrated remote and physical lab environments through (4) the development and implementation of two survey instruments.…”
Section: Introductionmentioning
confidence: 99%
“…While physical laboratories have been well researched from theoretical perspective through multiple types of student interactions (Komorek & Kattmann, 2008 ; Wei et al., 2018 ), such studies on remote laboratories are sparse (Wei et al., 2019 ). The significant contributions of this paper are (1) designing a remote lab such as RT-UTM that allows greater flexibility in performance of 5 experiments in comparison to its equivalent physical UTM lab, (2) capturing the structure and interactivity of PL-UTM and RT-UTM through the Transactional distance theory (TDT) and ultimately (3) conceptual understanding in remote vs physical and integrated remote and physical lab environments through (4) the development and implementation of two survey instruments.…”
Section: Introductionmentioning
confidence: 99%
“…In face-to-face laboratories, Student-Equipment Interactions and Indirect Interactions have mainly been neglected as compared with the two types of interpersonal interactions (Student-Student and Student-Instructor). Except for one article (Wei et al, 2018), no studies in science laboratories were found that included these types of interactions. It is suggested for curriculum designers and instructors to be aware of the importance of these two types of interactions (S-E and I-I).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…It was also concluded that in the biology laboratories, the TAs had more important influences than the laboratory content on the students' attitudes. Another example was made by (Wei et al, 2018), in which a self-designed pre-lab survey was conducted to collect information about the importance of interactions before the commencement of the laboratory, and a post-lab survey was used to measure the frequency of interactions after the completion of the laboratory activity. The results from the survey were validated by the results of on-site observations.…”
Section: Findings Of Interactions In Face-to-face Science Laboratoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al provide excellent insight into what undergraduates expect from interactions in their practical class, stressing that students perceive the pre-lab interaction with instructors as "mostimportant" (Wei et al, 2018). It is generally accepted that some form of pre-laboratory exercise can help students prepare for laboratory practical classes (Agustian & Seery, 2017;Chaytor, Al Mughalaq & Butler, 2017).…”
Section: Introductionmentioning
confidence: 99%